2013
DOI: 10.1603/en12225
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Teneral AdultAnoplophora glabripennis(Coleoptera: Cerambycidae): Time to Initiate and Completely Bore Out of Maple Wood

Abstract: Anoplophora glabripennis (Motschulsky) is an introduced invasive pest with the potential to devastate hardwood forests in North America. Using artificial pupal chambers, we documented the time required by teneral adults at three temperatures (20, 25, and 30 °C), 60-80% RH, and a photoperiod of 16:8 (L:D) h to initiate boring after eclosion and subsequently bore completely through a 7-mm (range, 3-11 mm) layer of Norway maple wood (Acer platanoides L.). In total, 218 laboratory-reared pupae from the Chicago, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…The lower development temperature obtained for C. welensii and P. myardi in the present study was 12 °C, which is similar to reported values for other xylophagous cerambycid species. Specifically, the laboratory‐determined minimum development threshold for M. galloprovincialis at the pupation stage obtained by Naves and Sousa () is 12.2 °C; those for A. glabripennis reported by Keena () and Sánchez and Keena () range from 9 to 13 °C; and that for Psacothea hilaris (Pascoe) found by Watari et al . () is 12.6 °C.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The lower development temperature obtained for C. welensii and P. myardi in the present study was 12 °C, which is similar to reported values for other xylophagous cerambycid species. Specifically, the laboratory‐determined minimum development threshold for M. galloprovincialis at the pupation stage obtained by Naves and Sousa () is 12.2 °C; those for A. glabripennis reported by Keena () and Sánchez and Keena () range from 9 to 13 °C; and that for Psacothea hilaris (Pascoe) found by Watari et al . () is 12.6 °C.…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, the CPE and cumulative DD data for the period 2002–2009 were fitted to a Gompertz equation as carried out previously by Smith et al . (); as well as by Keena () and Sánchez and Keena () for Anoplophora glabripennis (Motschulsky) (Coleoptera, Cerambycidae); by Stevenson et al . () for Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae); and by Knutson and Muegge () for Acrobasis casebearer nuxvorella (Neunzig) (Lepidoptera, Pyralidae).…”
Section: Methodsmentioning
confidence: 86%
“…The first pupae were found in the samples in mid June. The pupal stage in A. glabripennis lasts 47–54 days at 15 °C and, after eclosion, the adult remains in the pupal chamber for a further 12–14 days (at 20 °C) before it chews its way out and emerges from the wood (Keena & Moore, ; Sánchez & Keena, ). Thus, the individuals found as pupae in June are unlikely to have emerged as adults before mid‐August, and those pupae found in the samples in July and August would not have emerged and laid eggs until even later in the season.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae generally tunnel upwards for 10–30 cm and when fully grown; they excavate a slightly enlarged chamber at the end of the tunnel in which to pupate. The adult beetle emerges from the pupa inside the pupal chamber and, after waiting 12–14 days to harden its exoskeleton, it chews its way to the outside leaving behind a perfectly circular exit hole that is typically 10 mm in diameter (Haack et al ., ; Sánchez & Keena, ).…”
Section: Methodsmentioning
confidence: 99%
“…Fully grown larvae pupate in an enlarged chamber at the end of the feeding tunnel. The adult beetle emerges within this pupal chamber and then chews its way to the outside, through a circular exit hole that is typically 10 mm in diameter (Sánchez & Keena, ).…”
Section: Methodsmentioning
confidence: 99%